Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific - Gill, Anthony C.; Edwards, Alasdair J. (Zootaxa, 2003)
Pseudoplesiops wassi is described from 34 specimens, 17.7–28.8 mm SL, from throughout the West Pacific. It is closely related to P. collare from Indonesia, with which it shares 14 precaudal vertebrae (more than any other congener). It is distinguished from P. collare and all other congeners in having the following combination of characters: dorsal-fin rays I,27–29, usually I,28; pelvic-fin rays I,3; scales in lateral series 32–39, usually 33–36; and circumpeduncular scales 16.